2019
DOI: 10.1080/13504851.2019.1588939
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration economies in urban retailing: are there productivity spillovers when big-box retailers enter urban markets?

Abstract: Previous studies have found that big-box retail entry does not affect the productivity of incumbent retailers when entry occurs in urban areas. In this paper, we show that there are positive spillover effects of big-box retail entry for incumbent retailers in urban areas, but these effects are limited to relatively small retailers; thus, it is difficult to detect these effects in a full sample of firms by using traditional econometric methods, such as difference-indifference estimation. In a two-step procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The differentiated competition among enterprises drives the level of technological innovation in industry. Formal and informal learning exchange organizations within industry facilitate the generation and dissemination of new knowledge and help promote green technology R&D, thereby increasing GTFP [ 40 , 41 ].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…The differentiated competition among enterprises drives the level of technological innovation in industry. Formal and informal learning exchange organizations within industry facilitate the generation and dissemination of new knowledge and help promote green technology R&D, thereby increasing GTFP [ 40 , 41 ].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Gerben and Cees [ 23 ] found that the specialization externality of industrial agglomeration is obvious, while the diversification externality is not. Li et al [ 24 ] found that specialized agglomeration can promote the dissemination of creative knowledge, promote technical cooperation between enterprises, and also help to reduce transaction costs and improve transaction efficiency, which will undoubtedly have a positive impact on urban innovation. Another view is that Jacobs externalities are conducive to innovation.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%